2020
DOI: 10.1021/acsaem.0c01507
|View full text |Cite
|
Sign up to set email alerts
|

CdS Nanospheres Decorated with NiS Quantum Dots as Nobel-Metal-Free Photocatalysts for Efficient Hydrogen Evolution

Abstract: Noble-metal-free photocatalysts have attracted tremendous interest in recent years. Among them, cadmium sulfide (CdS) has been considered as one of the most important photocatalysts with potential applications in hydrogen evolution. However, its efficiency is relatively low due to the fast recombination of photogenerated charge carriers. In this work, defective CdS nanospheres were designed. NiS quantum dots were introduced to facilitate the efficient separation of photogenerated electrons and holes. Without n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…With the global energy crisis and environmental pollution, a great deal of money and manpower have been devoted to the great project of finding new sources of energy. , The application of solar energy is considered to be one of the most promising technologies to solve the above problems. , In particular, since Fujishima reported that the TiO 2 photoelectrode can decompose water to produce hydrogen under ultraviolet irradiation, many efforts have been made in photocatalytic hydrogen evolution. Since then, various semiconductor photocatalysts have been developed to advance this technology, such as CdS, NiS, g-C 3 N 4 , and so on. However, these semiconductors generally have the defect of rapid recombination of photogenerated charges, which results in low photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…With the global energy crisis and environmental pollution, a great deal of money and manpower have been devoted to the great project of finding new sources of energy. , The application of solar energy is considered to be one of the most promising technologies to solve the above problems. , In particular, since Fujishima reported that the TiO 2 photoelectrode can decompose water to produce hydrogen under ultraviolet irradiation, many efforts have been made in photocatalytic hydrogen evolution. Since then, various semiconductor photocatalysts have been developed to advance this technology, such as CdS, NiS, g-C 3 N 4 , and so on. However, these semiconductors generally have the defect of rapid recombination of photogenerated charges, which results in low photocatalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…39,46 Furthermore, no diffraction peak for AB was observed in the nanocomposites, which is probably due to the low content and crystallinity of AB and its high dispersion on the surface of the CNs. 14 In addition, no shi of the diffraction peak of g-C 3 N 4 was observed, indicating that the AB and NiS 2 nanoparticles loaded on the CNs did not changed the morphological structure of the CNs. From the above results, we found that the NiS 2 nanoparticles were successfully modied on the surface of the CNs-AB.…”
Section: Resultsmentioning
confidence: 95%
“…[10][11][12][13] Nevertheless, the photocatalytic performance of pure g-C 3 N 4 is constrained by its fast charge recombination, low surface area and narrow light absorption range. 10,14 As a result, various modication methods have been investigated to overcome these weaknesses, like constructing heterojunctions, element doping, cocatalyst loading, morphoregulation and so on. [15][16][17][18][19] Among these strategies, cocatalyst loading, such as with transition and noble metals, to improve the charge separation efficiency and solar energy utilization of pure g-C 3 N 4 is a particularly effective method.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the limitation of high price, extreme scarcity, and complicated synthetic processes affect the commercialization of current photocatalysts with the noble metals. Therefore, it is significant to develop high-performance CdS-based photocatalysts by coupling with low-cost materials, such as the transition metal sulfide [7][8][9][10], transition metal oxide [11,12], graphene oxide [13], hydroxide [14], carbide [15], etc.…”
Section: Introduction mentioning
confidence: 99%